PENGARUH DOSIS PUPUK BOKASI KOTORAN KAMBING DAN KOTORAN SAPI TERHADAP HASIL PRODUKSI TANAMAN TOMAT (Solanum lycopersicum L.) VARIETAS NEW MUTIARA F1 - Prananti, Fidyah Resti; Sunaryo, Yacobus; Darnawi, Darnawi (JURNAL ILMIAH AGROUST, 2018)
This study aimed to determine the dosage of bokasi fertilizer and the type of bokasi fertilizer that appropriate to increase the yield of tomato plants. The experiment was carried out at Pusat Pelatihan Pertanian Dan Pedesaan Swadaya (P4S) Lestari Makmur, Jl. Wates Km.12 Pollaman of Argorejo Village, Sedayu District, Bantul Regency, Yogyakarta. The research location has altitude of 149 meters above sea level, temperature 24.5 - 32.5 â„ƒ, the rainfall 1500 - 2000 mm per year and air humidity 65 -95%. The study was conducted in June - October 2018. The study was conducted by 3 Ã— 2 factorial experiment arranged in a completely randomized design with four replications. The first factor was the dosage of the bokasi fertilizer, which was 3, 6 and 9 ton.ha-1. The second factor is the type of bokasi fertilizer namely goat manure and cow dung. Observation variables included plant height, leaf number, flowering age, fruiting age, harvest age, number of fruits per plant, fruit weight per plant, fruit diameter, fresh weight and dry weight of plants. Analysis of the date using analysis of variance followed by Duncan's Multiple Range Test (DMRT) at a significant level of 5%. The results of the experiment indicated analysis showed no interaction between the dosage and the type of bokasi fetilizer to plant height, flowering age, fruiting age, plant fresh weight, plant dry weight and number of leaves. While there is an interaction between the dosage and the type of bokasi fertilizer on the number of fruits, fruit weight and diameter of the fruit. The highest yield was obtained on the type of goat manure bokasi with a dose of 9 tons. ha-1